LEGAL REGULATION OF FLEXIBLE WORKING HOURS: THE PROBLEMATIC ASPECTS - Vyshnovetska, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to identify the problematic aspects of the legal regulation of flexible working hours and to determine the ways to overcome them. Research methods: documentary analysis and synthesis, comparative analysis, cognitive-analytical, as well as methods of systematization and generalization. Results: problematic aspects of the legal regulation of flexible working hours under the legislation of Ukraine were analysed using the example of judicial practice. Discussion: a need to improve the legal regulation of this sphere of relations at the local level is discussed. Information and communication technologies have changed the ratio of territorial, temporal and organizational characteristics of work. A flexibility of the work modes could be considered from the point of view of its structural elements: flexibility of the workplace and flexibility of the working hours. A variety of types of the flexible working hours and forms of the remote employment used in practice is explained, on the one hand, by the desire of organizations to adapt to the changing conditions of the external environment, associated with the strengthening of the processes of globalization of the economy, the development of information and communication technologies and Internet business, and on the other hand, by a necessity to meet the needs of the employees who seek to ensure a balance between work and personal time. Therefore, the flexible mode of work in the practice of modern organizations is no longer an exception to the rules, but a trend that strengthens and determines the vector of development. An author notes that in the modern period, a completely different idea on the organization of the working hours was formed. It assumes that employees are professionally autonomous in the organization and use of their working hours, they are responsible for its planning. It was concluded that the main problem of the legal regulation of flexible working hours is the development of local regulation, in particular, the regulation of issues regarding the relationship between the employee’s right to autonomy in the organization and the use of his/her working hours and the obligation to be in contact with the employer, as well as the implementation of monitoring and observation the productivity and working hours of the employees. These issues should be clearly regulated in the local acts of the employer.